1986
DOI: 10.1007/bf00584938
|View full text |Cite
|
Sign up to set email alerts
|

Intraepithelial current flow in rat pancreatic secretory epithelia

Abstract: To assess the importance for transepithelial salt secretion of current flow across the baso-lateral membrane, we studied the effects of ouabain (1 mmol/l), Ba (3 mmol/l) and tetraethylammonium (TEA: 10 mmol/l) on secretion by the acinar (caerulein stimulated) and ductal (secretin stimulated) epithelia of the perfused rat pancreas. Within 10 min, ouabain caused a 79% inhibition of acinar secretion which was resolvable into two exponentials with half-times, respectively, of 0.24 min +/- 0.19 (S.D.) and 6.40 +/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1989
1989
1996
1996

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…Thus, secretin-stimulated fluid transport should be reduced if the basolateral K+ channels are blocked, and this is exactly what we found when ducts were exposed to barium or TEA. Previously, it has been reported that these blockers (at the same concentrations we have employed) have no effect on fluid transport from the perfused rat pancreas stimulated with secretin, at least over a 10 min exposure period (Evans, Pirani, Cook & Young, 1986). It is possible that during our longer, 1 h exposure time, TEA and barium have toxic effects on the duct cells.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, secretin-stimulated fluid transport should be reduced if the basolateral K+ channels are blocked, and this is exactly what we found when ducts were exposed to barium or TEA. Previously, it has been reported that these blockers (at the same concentrations we have employed) have no effect on fluid transport from the perfused rat pancreas stimulated with secretin, at least over a 10 min exposure period (Evans, Pirani, Cook & Young, 1986). It is possible that during our longer, 1 h exposure time, TEA and barium have toxic effects on the duct cells.…”
Section: Discussionmentioning
confidence: 80%
“…During perfusion with Ba2+ alone flow rate was rapidly and almost completely inhibited in contrast to the results shown in this figure. We interpret this inhibition as a side-effect of the increase in intraglandular pressure (but see Evans, Pirani, Cook & Young, 1986). 1 /M-verapamil alone had no effect on flow rate or electrolyte composition.…”
Section: The Effects Of Bariummentioning
confidence: 99%
“…Such an effect would explain the dosedependent increase in pancreatic juice K + concentration (from 5 to 10 raM) that has been shown to occur following stimulation of the rat pancreas with secretin [33]. Although it has been reported that Ba 2+ has no effect on secretin-stimulated fluid secretion from the perfused rat pancreas [9], this could be explained by poor uptake of Ba 2 § into the duct cell since it is thought to block the channel from the inside face of the plasma membrane [39].…”
Section: Discussionmentioning
confidence: 94%